Semi Quantitative Risk Assessment Evaluation of Histamine on Pindang Cakalang Product in Jakarta - Anne Mumtaza Putri (Universitas Sumatera Selatan, 2023)
Pindang is a traditional processed fish product produced from skipjack tuna. Pindang cakalang is a processed product that is very popular DKI Jakarta villager with a high level of consumption. Skipjack tuna is one of family of scrombroidae which has red meat, skipjack tuna damaged by bacteria or enzymes that can produce toxins called scrombotoxins. The toxic compound is histamine. The danger of histamine in skipjack tuna is included in the category of food safety hazards because it can provide toxic effects on the body, the investigation and assessment of the risks becomes very important. The purpose of this study is the risk in the skipjack tuna screening process in the DKI Jakarta area to control the danger of histamine. This study uses secondary and semi-quantitative data publications using risk ranger. The results of the risk analysis show a histamine hazard risk rating of 62. This indicates the hazard risk posed to the people of DKI Jakarta is included in the high category. The estimated population of DKI Jakarta that can question illness due to danger is 820,000 people / year from 9,108,732 inhabitants.